The Influence of Academic Supervision, Teacher Understanding of Special Needs Education, and Universal Design for Learning on the Implementation of Inclusive Education in Kindergarten - Karyawati, Efrilia; Hermanto, Hermanto (Journal of Innovation and Research in Primary Education, 2025)
Inclusive early childhood education demands not only equitable access but also teacher competence and adaptive instructional leadership. This study investigates the relationship between academic supervision and teachers’ understanding of children with special needs (SEN) and the Universal Design for Learning (UDL) framework within an inclusive kindergarten context. Employing a quantitative approach, the research involved 10 early childhood teachers at TK Khalifah, East Kutai, Indonesia. Data were collected through validated questionnaires, structured interviews, document analysis, and observation. The instruments measured two main variables: academic supervision and teacher understanding of SEN and UDL. Descriptive analysis showed that both variables predominantly fell into the moderate category. Inferential analysis using Pearson correlation revealed a strong positive relationship (r = 0.81) between academic supervision and teacher understanding, with a coefficient of determination (R²) of 86.6%. These findings suggest that academic supervision makes a significant contribution to teachers’ inclusive competence. However, the moderate performance trends may reflect limited access to structured professional learning and the absence of contextual variables such as prior training or institutional support. The study concludes that differentiated, reflective, and collaborative supervision is crucial for advancing inclusive practices. Practical implications include the need for enhanced supervisory models and targeted professional development for early childhood educators. This research offers empirical insights to inform inclusive education policy and instructional leadership in early learning environments.